2014
DOI: 10.1016/j.cattod.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrodeoxygenation of lignin-related 4-propylphenol into n-propylbenzene in water by Pt-Re/ZrO2 catalysts

Abstract: Abstract:Bimetallic Pt-Re/ZrO 2 catalysts were developed for the selective hydrodeoxygenation of 4-propylphenol as a lignin model to n-propylbenzene in water. The addition of Re to Pt/ZrO 2 improved the catalyst stability and product selectivity. Reaction temperature greatly affected not only reaction efficiency but also product distribution. n-Propylbenzene was obtained in up to 73% yield with ca. 80% selectivity. After the reaction, the catalyst was deactivated possibly due to waterinduced wrapping of Pt nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 44 publications
(42 reference statements)
3
43
0
Order By: Relevance
“…Consequently synergistic effects can be observed which lead to improved catalytic activity, selectivity and even stability [98]. In fact, bimetallic catalysts are widely used and have proven records in a number of industrial processes [66,67,99]. However, the feasibility and effectiveness of the bimetallic strategy has not been investigated for lignin hydrogenolysis until recently.…”
Section: Bimetallic Systems In Lignin Hydrogenolysismentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently synergistic effects can be observed which lead to improved catalytic activity, selectivity and even stability [98]. In fact, bimetallic catalysts are widely used and have proven records in a number of industrial processes [66,67,99]. However, the feasibility and effectiveness of the bimetallic strategy has not been investigated for lignin hydrogenolysis until recently.…”
Section: Bimetallic Systems In Lignin Hydrogenolysismentioning
confidence: 98%
“…Various strategies including thermal decomposition [11,62], oxidation [63,64], hydrogenolysis [65][66][67], decarboxylation and decarbonylation were employed to convert lignin model compounds or real lignin into aromatics [68], solvents, liquid fuels, bioethanol or other valuable chemicals. Among these methods, hydrogenolysis of C-O linkages in lignin, in which H 2 is used to cleave the C-O bond over a metal catalyst, is regarded as an effective way to transform lignin into depolymerized aromatic platform compounds.…”
Section: Lignin Hydrogenolysis: Overviewmentioning
confidence: 99%
“…Considering that the bond dissociation energy of C aromatic -OH is 84 kJ/mol higher than that of C aliphatic -OH (Furimsky, 2000), it has been suggested that the formation of aromatics is through the HYD path instead of the DDO path (Ohta et al, 2014). In the presence of acid sites, phenol is first hydrogenated to cyclohexanol, then dehydrated to cyclohexene, and finally dehydrogenated to benzene (Ohta et al, 2014) following the HYD path.…”
Section: Kinetic Fittings and Reaction Network Analysismentioning
confidence: 98%
“…In the presence of acid sites, phenol is first hydrogenated to cyclohexanol, then dehydrated to cyclohexene, and finally dehydrogenated to benzene (Ohta et al, 2014) following the HYD path. In this mechanism, cyclohexene is the key intermediate that determines the final distribution of benzene/cyclohexane.…”
Section: Kinetic Fittings and Reaction Network Analysismentioning
confidence: 99%
See 1 more Smart Citation